Clinical phenotype and management of individuals with mosaic monosomy X with Y chromosome material stratified by genital phenotype. Issue 5 (22nd February 2021) - Guzewicz, Lindsey; Howell, Susan; Crerand, Canice E.; Umbaugh, Hailey; Nokoff, Natalie J.; Barker, Jennifer; Davis, Shanlee M.
Abstract: Individuals mosaic for monosomy X and a cell line with Y chromosome material can have genitalia that appear phenotypical female, male, or ambiguous. Those with this karyotype and typical female genitalia are diagnosed with Turner syndrome; however, this definition specifically excludes those with genitalia other than typical female. There is limited information on whether medical and neurodevelopmental risks are similar among individuals with monosomy X and Y chromosome material across genital phenotypes. This multicenter retrospective study compared comorbidities and clinical management in individuals with monosomy X and Y material and male/ambiguous genitalia to those with typical female genitalia. Electronic medical records for all patients with monosomy X and Y material (n = 76) at two large U.S. pediatric centers were abstracted for predetermined data and outcomes. Logistic regression was used to compare the two phenotypic groups adjusting for site and duration of follow‐up. The male/ambiguous genitalia group was just as likely to have congenital heart disease (RR 1.0, 95%CI [0.5–1.9]), autoimmune disease (RR 0.6 [0.2–1.3]), and neurodevelopmental disorders (RR 1.4 [0.8–1.2]) as those with female genitalia. Despite similar risks, they were less likely to receive screening and counseling. In conclusion, individuals with monosomy X and Y chromosome material have similar medical and neurodevelopmental risks relative to individuals with Turner syndrome regardless of genitalia, but there are notable differences in clinical management.